Protection of the Customary Land of the Baduy Indigenous Peoples as One of the Supporting Factors for Local Food Security in the Banten Region - Jarkasi Anwar; Muhamad Muslih (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The Baduy indigenous people as one of the ethnic groups in Indonesia have various unique and diverse cultural characteristics. The ethnic groups in Banten for hundreds of years have had their main livelihood, namely farming (ngahuma) and gardening to maintain survival in obtaining food so that this ngahuma is a form of food security for the Baduy indigenous people. Some of the Baduy's ulayat land is used for ngahuma and gardening. Recently, there has been an abuse of Baduy ulayat land by some irresponsible people. Mursyid's father as a traditional leader of the Inner Baduy does not agree with the existence of illegal gold mining around the Baduy area. This will disturb the land and forest ecosystems, especially since these customary rights are in the upstream area which will certainly cause negative things for the Baduy people. The gold mining will cause negative things for the environmental ecosystem in the Baduy area and even threaten the forests protected by the government. Baduy rejects the existence of gold mining if foreign companies exploit it. The expression of one of the Baduy community leaders, "We are the trust of our ancestors, bisi ayeuna Gunung kalebur lebak karuksak karobah great-grandmother, ayeuna proof of Mount Liman menta tulung, menta guarded really I pamarentah".This study describes the exploitation of gold mining around the customary rights area in the Baduy area as well as legal protection efforts from the government for the abuse of the customary rights residential area of the Baduy Indigenous People.The long-term goal to be achieved from this research is to obtain an overview of the current condition of the customary lands of the Baduy people inside and outside the Baduy so that the government can take a stand, help maintain and prevent gold mining activities in the area of customary rights of Baduy from being disturbed. outsiders.The specific target to be achieved from this research is to ensure that the Baduy community can use food land for ngahuma and gardening to the maximum so that the food security of the Baduy indigenous peoples is maintained.This research uses normative juridical and sociological normative legal research methods. This research is descriptive analytical and uses primary data sources and secondary data sources. Descriptive in this study is a description of the situation, condition, condition, and reality of ulayat land or customary land in the Baduy community which is misused by irresponsible elements so that it has a major impact on the food security of the Baduy community. Then analyze what the problem is in order to find a solution to the problem. Sources of data used in this study were obtained from Library Research (Library Research). Normative Jurisdiction in this study is a discussion of several existing regulations. Sociological Normative Research on law constructs law as a system of laws and regulations that have existed so far and then constructed in a society's behavior. This study also uses primary data sources and secondary data which are analyzed using qualitative methods, with data collection techniques from library studies and field studies to the Inner Baduy and Outer Baduy. Interviews and observations were conducted to obtain the necessary data. The data obtained through field research and literature study were analyzed in a qualitative normative manner to obtain clarity on the problems to be discussed.